Evaluation of the properties and storage stability of EVA polymer modified asphalt - M Al-Layla; Adil Hussien; Eman Mjthab (College of Education for Pure Sciences, 1999)
ABSTRACT Polymers are being increasingly used for modification of Asphalt to enhance highway pavement performance. This paper describes the polymer modification of two penetration grade Asphalt with ethylene vinyl acetate (EVA). Two base asphalt from two crude oil sources (Baiji paraffinic asphalt & Qaiyarah aromatic asphalt) were mixed with ethylene vinyl acetate (EVA) at different polymer content. The physical properties including softening point, penetration at 25°C, and ductility of the basic asphalt and ethylene vinyl acetate modified asphalt were studied. It has been observed that the softening point has increased on the other hand, the penetration and ductility values has decreased according to the test results. The effect of storage time on uniformity at higher temperature was studied by storage stability test .